A Novel Combination of Pre-, Pro-, and Postbiotics Modulates Bacterial Diversity and Composition In Vitro. (14th June 2022) - Vance, Arianne; Raut, Shilpa; Sharafi, Mastaneh; Alamdari, Nima; Grier-Welch, Adeline
Abstract: Objectives: To test the effect of probiotic strains ( Lactobacillus rhamnosus GG and Bifidobacterium animalis subsp. lactis BB-12 ), a prebiotic (bacteriophage blend), and a postbiotic (tributyrin) on the human intestinal microbiota in vitro. Methods: Short term colonic incubation was performed under conditions representative of the proximal large intestine, using the fecal microbiota of a single healthy human donor. At the start of the experiment, treatments and a blank control were added to the reactors. Each reactor also received a carbohydrate-supplemented nutritional medium and freshly prepared fecal inoculum. Reactors were closed with a rubber septum, made anaerobic through flushing with nitrogen, and incubated for 48 hours. Each condition was run in triplicate. Changes in microbial community composition were determined via 16S-targeted Illumina sequencing and flow cytometry. Enriched bacterial genera were identified using LEfSe (LDA > 2, p < 0.05). Results: A significant increase in alpha-diversity was observed by 48h compared to the control. LEfSe revealed that community shifts were attributed to a wide range of bacterial genera including Gemmiger, Lactobacillus, Bacteroides, Eubacterium, Oscillibacter, and Holdemanella at 24h and of genera such as Lactobacillus, Bacteroides, Muribaculum, and Holdemanella at 48h. LGG and BB-12 were not detected in the donor microbiota originally but abundance of both was higher after incubation. Conclusions: The results from this study suggest that a combination of pre-, pro-, and postbiotics modulates gut microbiota by increasing microbial diversity and the relative abundance of a number of bacterial genera. An increase in the abundance of LGG and BB-12 indicates growth of these strains in the presence of a human gut microbiota. Future human clinical studies are needed to further investigate the observed effects. Funding Sources: The study was conducted by an independent lab, ProDigest, and funded and sponsored by Ritual (Natals, Inc.). Compound Solutions, Inc. also financially supported the study.